2011
DOI: 10.1007/s00221-011-2680-5
|View full text |Cite
|
Sign up to set email alerts
|

Misjudging where you felt a light switch in a dark room

Abstract: Previous research has shown that subjects systematically misperceive the location of visual and haptic stimuli presented briefly around the time of a movement of the sensory organ (eye or hand movements) due to errors in the combination of visual or tactile information with proprioception. These briefly presented stimuli (a flash or a tap on the finger) are quite different from what one encounters in daily life. In this study, we tested whether subjects also mislocalize real (static) objects that are felt brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Dassonville (1995) was the first to study tactile localization during arm movements. Interestingly, he reported more pronounced errors than in the present and other related studies (Maij et al 2011b;Watanabe et al 2009). One possible reason could be differences in arm velocity.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Dassonville (1995) was the first to study tactile localization during arm movements. Interestingly, he reported more pronounced errors than in the present and other related studies (Maij et al 2011b;Watanabe et al 2009). One possible reason could be differences in arm velocity.…”
Section: Discussionsupporting
confidence: 50%
“…When the arm is moving, the tactile input in the brain needs to be combined with dynamic information (i.e., proprioceptive feedback or efferent motor commands) about the ongoing arm movement to provide veridical spatial information in external coordinates. The present report addresses how the brain combines these signals in dynamic tactile localization.The few previous studies on dynamic tactile localization have shown that subjects systematically misperceive the location of tactile stimuli presented near the time of an arm movement (Dassonville 1995;Maij et al 2011b; Watanabe et al. 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As efferent information leads a movement, and afferent information is delayed with respect to the movement, the two might be in conflict during the movement (e.g. [28]). This conflict in position judgment during a movement might be one of the reasons why the movement paths are disturbed, without effects on the proprioceptive position sense at the endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some data suggest that similar phenomena also occur around the time of hand movements, when tactile stimuli are systematically mislocalized in the direction of the movement (Dassonville, 1995;Watanabe et al, 2009;Maij et al, 2011) and perceptually delayed with respect to the subjective onset time of the movement (Dassonville, 1995;Jackson et al, 2011). This suggests that similar strategies may be exploited by different sensorimotor systems during the active exploration of the environment.…”
Section: Introductionmentioning
confidence: 94%